Efforts to Improve Teachers' Competence in Developing Learning Sources and Media With The Think Pair and Share Model Discussion - Sukamto Sukamto (Politeknik Siber Cerdika Internasional, 2022)
The general research objective is to determine the level of teacher skills in developing learning resources and media after supervision of the Think Pair and Share model. In particular, this study aims to improve the skills of teachers in developing learning resources and media through the supervision of the Think Pair and Share model.The research subjects were teachers of SD Negeri 1 Klego, Klego District, Boyolali Regency, totaling 7 people. The type of research is school action research. Data collection techniques used: questionnaires, observations, interviews, and documentation. The data analysis technique used descriptive qualitative.The results of the study concluded: (1) Think Pair and Share model was able to increase the active participation of teachers to exchange ideas and experiences, increase reciprocal interaction between teachers, increase openness among teachers, increase teacher understanding of the problems encountered in the learning process; (2) Think Pair and Share model is very effective to improve the skills of teachers in developing learning resources and media, because all teachers respond with high categories. In other words, the teacher feels that supervision with the Think Pair and Share model is very useful for improving learning resources and media.